Identification of epidemic scarlet fever group A Streptococcus strains in the paediatric population of Houston, TX, USA. Issue 10 (26th October 2021) - Cubria, M. Belen; Delgado, Jose; Shah, Brittany J.; Sanson, Misu A.; Flores, Anthony R.
Abstract : Scarlet fever (SF) has recently been associated with group A streptococcal (GAS) strains possessing multidrug resistance and specific streptococcal exotoxins. We screened a local surveillance collection of GAS emm12 strains in Houston, TX, USA for antimicrobial resistance and identified a single isolate matching the antimicrobial resistance pattern previously reported for SF clones. Using whole-genome sequencing and combining genome sequence data derived from national surveillance databases, we identified additional emm12 GAS clones similar to those associated with prior SF outbreaks, emphasizing the need for continued surveillance for epidemic emergence in the USA.